Impact of Competitive Advantage and Risk on Market Performance : A Study of Top 20 Companies as per Market Capitalization - Sar, Ashok K. (Indian Journal of Finance, 2019)
The paper investigated the impact of competitive advantage and risk on market performance of top 20 companies globally. The companies were chosen based on their rankings on market capitalization during the financial year 2016 - 17. The study was based on the analysis of disclosed financial and market data using correlation and regression analysis in SPSS. The quantitative approach provided a better understanding of all the dynamics, complexities, and problems that characterized companies with high market capitalization. I used financial data from the annual reports of the companies, and market data from stock market sources. The results suggested that leverage had the greatest impact on market performance.